Motivators and barriers towards clinical research participation: A population-based survey from an Arab MENA country - Kamal M. Al-Shami (12936653) (2022)
Jordan was the first Arab country to enact clinical research regulations. The country has a well-flourished pharmaceutical industry that leans heavily on clinical research (CR) for drug development and post-marketing surveillance. In this cross-sectional study, we sought to assess the public’s awareness and attitude towards CR as well as their perceived motivators and barriers to CR participation. A population-based, self-administered questionnaire was distributed to the general public in Jordan. Among the 1061 participants in this survey, 74% reported being aware of CR. The majority (70%) agreed to the role of CR in health promotion. Online information and healthcare staff were the two main sources of CR information for the participants. About 25% of the participants received prior invitations to participate in CR with 21% agreeing to participate. However, most participants of the current study (63%) were willing to participate in future CR. Contributing to science, benefiting others, and promoting one’s own health were the top motivating factors for participating in CR; while time constraints, fear of research procedure, and lack of interest were the most cited reasons for rejecting participation. Filling out questionnaire surveys, donating blood samples, and participating in physical examinations were the main CR contributions of the participants. Nearly 31% of the participants believed that CR is conducted in a responsible and ethical manner, while 57% did not have an opinion regarding the same matter. In addition, 49% and 44% were neutral with regards to the degree of harm and confidentiality posed by CR. While only 27% disagreed that CR exposes participants to some form of harm, 48% either strongly agreed (15%) or agreed (33%) that it maintains high level of confidentiality for participants. The current study provides insight into the public’s perception of CR in Jordan as well as its motivating factors and perceived barriers towards participating in CR. We envisage to utilize this insight as an aid in the design of vigilant future awareness campaigns and recruitment strategies. Other Information Published in: PLOS ONE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1371/journal.pone.0270300